Artificial exosomes mediated spatiotemporal-resolved and targeted delivery of epigenetic inhibitors - Huan Li (BMC, 2021)
Abstract Background Malignant tumor is usually associated with epigenetic dysregulation, such as overexpression of histone deacetylase (HDAC), thus HDAC has emerged as a therapeutic target for cancer. Histone deacetylase inhibitor has been approved for clinical use to treat hematological cancers. However, the low solubility, short circulation lifetime, and high cytotoxicity partially limited their applications in solid tumor. Methods The upconversion nanoparticles (UC) modified with mesoporous silica (SUC) was used to load an HDACI, suberoylanilide hydroxamic acid (SAHA), and further camouflaged with M1 macrophage-derived exosome membranes (EMS). EMS was characterized in size and compositions. We also analyzed the epigenetic regulation induced by EMS. Furthermore, we evaluate the biodistribution and in vivo tumor inhibition after the systemic administration of EMS. Results This novel style spatiotemporal-resolved drug delivery system, EMS showed a high loading efficiency of SAHA. EMS could be taken up by lung cancer cells and lead to efficient epigenetic inhibition. We found that the integrin α4β1 on M1-EM, was crucial for the homing of EMS to tumor tissues for the first time. In tumor-bearing mice, EMS showed spatiotemporal-resolved properties and facilitated the drug accumulation in the tumors, which induced superior anti-tumor effects. Conclusion This novel style of spatiotemporal-resolved nanoparticles can be used as a theranostic platform for lung cancer therapy. Graphical Abstract